Common features and differences of the hypothalamic–pituitary–gonadal axis in male and female. (15th September 2014) - Dagklis, Themistoklis; Ravanos, Kostas; Makedou, Kali; Kourtis, Anargyros; Rousso, David
Abstract: Male and female reproductive axis, comprised of hypothalamus, pituitary and gonads, present common features and differences, discussed in this review. These include the way hypothalamus regulates pituitary function, and the way pituitary, in turn, affects gonadal function. Finally, age plays an important role in axis regulation, in both genders. Chinese abstract: 男性与女性的生殖轴均由下丘脑、垂体、性腺组成，本文将阐述它们间存在的相似与不同之处，包括下丘脑对垂体的调控以及垂体作为应答对性腺的作用。最后，年龄是影响男女性腺轴调节的重要因素。